HUBUNGAN PENGETAHUAN IBU NIFAS TENTANG PERAWATAN PAYUDARA TERHADAP PRODUKSI ASI DI KECAMATAN TAPUNG - Nova Yulita; Sellia Juwita (Collaborative Medical Journal, 2023)
Knowledge about breast care has an important role for mothers to see the smooth flow of milk during the puerperium. Mothers who have good knowledge in breast care will influence the behavior and attitude of the mother towards the convenience of the mother in carrying out breast care to expedite milk production. The purpose of this research is to find out whether there is a relationship between mother's knowledge about breast care and breastfeeding in Tapung District. The type of research used is quantitative analytic research with a cross sectional approach. Sampling in this study used a side accidental technique with a total of 51 people. Bivariate analysis data processing using chi-square test. The results of the chi-square statistical test showed that there was a relationship between mother's knowledge about breast care and the smoothness of breastfeeding in postpartum mothers with a p-value <0.05. Good knowledge changes the mother's attitude towards breast care in postpartum mothers so that the mother's milk production runs smoothly.